2003
DOI: 10.1068/p5019
|View full text |Cite
|
Sign up to set email alerts
|

Judging Distance across Texture Discontinuities

Abstract: Sinai et al (1998 Nature 395 497-500) showed that less distance is perceived along a ground surface that spans two differently textured regions than along a surface that is uniformly textured. We examined the effect of texture continuity on judged distance using computer-generated displays of simulated surfaces in five experiments. Discontinuities were produced by using different textures, the same texture reversed in contrast, or the same texture shifted horizontally. The simulated surface was either a ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
36
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 28 publications
13
36
1
Order By: Relevance
“…Our results concur with those of an increasing number of studies in recent years demonstrating the importance of the ground surface in scene perception (e.g., Feria et al, 2003;Meng & Sedgwick, 2001Ni et al, 2004Ni et al, , 2005Ni et al, , 2007Ooi et al, 2001;Sinai et al, 1998;. Future studies are needed to examine the relative influence of type of surface (ground vs. ceiling) and location in the visual field in other visual tasks, such as visual search and absolute and relative distance judgments.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our results concur with those of an increasing number of studies in recent years demonstrating the importance of the ground surface in scene perception (e.g., Feria et al, 2003;Meng & Sedgwick, 2001Ni et al, 2004Ni et al, , 2005Ni et al, , 2007Ooi et al, 2001;Sinai et al, 1998;. Future studies are needed to examine the relative influence of type of surface (ground vs. ceiling) and location in the visual field in other visual tasks, such as visual search and absolute and relative distance judgments.…”
Section: Discussionsupporting
confidence: 80%
“…This discontinuity effect was also found by J. Wu, Z. J. He, and Ooi (2002) using virtual reality displays, and by Feria et al (2003) using computer-simulated scenes. Z. J.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Whereas previous studies (Feria et al, 2003;He & Nakayama, 1992, 1994a, 1994bMeng & Sedgwick, 2001Sinai et al, 1998) revealed the importance of a surface, especially a ground surface, in organizing 3-D scenes, our results, together with those of McCarley and He (2000), point to a unique role for the ground surface, among all environmental surfaces, in the perception of the visual world. However, the question of what leads to this dominance of the ground surface needs to be answered.…”
Section: Discussioncontrasting
confidence: 51%
“…They found that perceived distance, measured either by perceptual judgments of absolute distance or visually cued blind walking, was accurate on a continuous ground surface, underestimated when the ground surface was composed of two distinct textured regions, and overestimated when the ground surface was interrupted by a gap. Feria, Braunstein, and Andersen (2003) used a computergenerated display to examine this "discontinuity effect" and found that it exists even when the same texture is present in both regions, but one region is offset horizontally to produce an implicit contour.…”
mentioning
confidence: 99%